Ultrasound‐guided cannulation for medical students. (9th February 2021) - Armson, Andrew M.; Moynihan, Robert; Stafford, Nicholas; Jacobs, Chris
Abstract: Background: There is growing recommendation to integrate ultrasound training into undergraduate medical curricula; with limited evidence of its implementation in the United Kingdom. Peripheral intravenous cannulation (PIVC) often has high failure rates—particularly for patients with difficult vascular access. Ultrasound‐guided PIVC (US‐PIVC) has been shown to increase the rates of success and may reduce dependence on seniors. Teaching US‐PIVC to senior medical students may prove a clinically valuable and feasible means of introducing ultrasound into medical programmes. Methods: We initially surveyed 18 doctors to assess their perceptions and experience of ultrasound. Thirty‐five final‐year medical students took part in a novel US‐PIVC course. Students' competence was assessed at the end of the session using an objective assessment. Students' pre‐ and post‐course attitudes and confidence were evaluated using questionnaires. Results: All doctors surveyed reported difficulty performing PIVC since starting work: 66% on a monthly basis. None of the students (0%) and 11% of the doctors had previously received ultrasound training. By the end of the course, all students 'agreed' or 'strongly agreed' that the session was enjoyable and that they felt confident performing US‐PIVC. Thirty‐four of 35 participants attained the minimum competence standard. Students' confidence performing PIVC, regardless of ultrasound guidance, increased significantly ( p = 0.002) following the session. Discussion: As ultrasound becomes a more readily available point‐of‐care technology, it should be considered for inclusion in the undergraduate medical curriculum. Our course appears to be an effective model of teaching US‐PIVC to final‐year medical students. Similar courses could act as a pragmatic and clinically rewarding means of implementing US‐PIVC teaching into the latter years of undergraduate curricula.